IMPLEMENTASI KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH DI SMK NEGERI 2 BISNIS MANAJAMEN JAYAPURA PROVINSI PAPUA - Lobo, Daniel; Mataputun, Yulius; Tanta, Cornelius (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2021)
This study aims to describe the implementation of the principal's entrepreneurial competence in innovations, committed, being highly motivated, persistent and creative for effective solutions, and having an entrepreneurial ability in managing the activities of the production unit at SMK Negeri 2 Bisnis Manajemen Jayapura. This study uses a qualitative descriptive approach to a case study design. The research participants are principals, parents, alumni, students, and the Business and Industrial World (DUDI). Data collection techniques used participatory observation, in-depth interviews, and documentation study. The validity data test using data credibility techniques, namely triangulation and peer discussion. The data analysis uses an interactive pattern with the stages of data reduction, data display, and drawing conclusions/verification. The results of this study conclude that in general the principal, in his leadership has implemented entrepreneurial competencies such as innovations, committed, being highly motivated, persistent and creative for effective solutions) well, which is manifested in various forms of activities, including SMK Mart and travel agents business division, team work through the ISO 9001-2015 mechanism, environmental management, increasing the competence of teachers and students, as well as collaborating with DUDI.Keywords: implementation; competence; entrepreneurship; school principal